Enhancement of MODENAS CT115'S motorcycle muffler performance by optimization of backpressure. (November 2019) - Rojan, M A; Alias, Z; Bakar, S A; Hashim, S
Abstract: A research study on the enhancement of motorcycle muffler to improve MODENAS CT115's engine performance was conducted. To obtain the optimum value of backpressure, velocity, and temperature, the hole diameter of perforated tube has been modified. The modifications made for each design by increasing the hole diameter to the front and back of the perforated tube. Both the original muffler and modified designs were tested to obtain optimum pressure values through the ANSYS Fluent simulation. According to the theory, the value of the hole diameter will affect the backpressure value in the muffler, hence enable design optimization for achieving the best engine performance. The largest hole diameter for perforated tube on the front shows the lowest backpressure from the results obtained. The percentage improvement for design 4 is 10.3% higher than design 1, design 2 and design 3.